The Relationship Between Housing Physical Conditions and the Incidence of Acute Respiratory Infections (ARI) Among Coastal Communities in Medan City - Arrazy, Syafran; Hidayat, Baihaqy Azro (Poltekkes Kemenkes Bengkulu, 2025)
Dengue Hemorrhagic Fever (DHF) remains a significant public health issue in Indonesia, including in the working area of UPT Puskesmas Teluk Putat, Labuhan Batu Regency. Poor environmental conditions such as substandard housing, open water containers, and inadequate waste management increase the risk of DHF transmission. This study aimed to analyze the relationship between environmental sanitation and DHF incidence using a case-control approach. A total of 63 respondents were involved, consisting of 21 DHF cases and 42 controls in a 1:2 ratio. Data were collected through structured questionnaires, environmental observations, and secondary data from the health center. The results showed a significant association between water storage conditions (p = 0.019; OR = 3.76; 95% CI: 1.25–11.34) and waste management (p = 0.000; OR = 10.00; 95% CI: 2.96–33.78) with DHF incidence. However, housing conditions were not statistically significant (p = 1.000). These findings suggest that specific aspects of environmental sanitation, particularly water and waste management, play a critical role in DHF prevention. It is recommended that DHF control programs focus more on public education regarding environmental hygiene and strengthening household-based preventive behavior.